Electromyographic evaluation of the temporal muscle after the use of interocclusal splints with a vibrating device in individuals with sleep bruxism - Gomes, C. A. [UNESP]; Nascimento, L. F C; Brandão, J. G T [UNESP] (My University, 2009)
This is the first study performed with an interocclusal splint with a vibrating device on patients with sleep bruxism. The purpose of the present study was to evaluate the effectiveness of the splint with vibrating device on patients who suffer from sleep bruxism through computerized electromyography (EMG) of the anterior temporal muscles. Eight male and female patients, ranging in age from 18 to 28 years, with evident signs and symptoms of bruxism were selected. The splint were made for the upper arch. The patients was treated with the interocclusal splint with a vibrating device, and submitted to EMG evaluations of the anterior temporal muscles on both sides. The evaluations were performed at the beginning of treatment and after 21 days of splint use. Electromyography was performed in an isometric contractions measuring of the temporal muscles. The following results obtained revealed that: when closing the mandible (isometric contraction), the anterior temporal muscles had an expressive reduction in electromyographic activity (p. < 0.10), so this splints were considered effective for patients who suffer from sleep bruxism. © 2009 Springer-Verlag.
Keywords: Electromyography (EMG); Interocclusal splints; Temporomandibular joint disorder; Electromyographic; Electromyographic activity; Isometric contractions; Temporal muscle; Temporomandibular joint disorders; Vibrating devices; Biomedical engineering; Biophysics; Joints (anatomy); Ophthalmology; Sleep research; Muscle